Iron biofortification potential of siderophore producing rhizobacterial strains for improving growth, yield and iron contents of groundnut. (15th July 2022) - Sarwar, Sair; Khaliq, Abdul; Yousra, Munazza; Sultan, Tariq
Abstract: Biofortification in crops is an effective and sustainable approach to reduce global malnutrition. Groundnut ( Arachis hypogea L.) is inherently low in micronutrients, especially iron. A greenhouse study was conducted to evaluate the effect of siderophore producing bacterial strains (SPBs) on growth, yield and iron content of groundnut. Three efficient SPBs identified as Bacillus subtilis and their consortia were used alone and with soil or foliar applied iron. The results revealed that the inoculation of SPBs alone and combination with soil applied Fe, showed maximum relative increase of 63 and 86 percent in shoot fresh and dry weight respectively. Likewise, the number of pods plant −1, pod weight plant −1, 20 pod length and 100 kernel weight of groundnut were increased significantly in response to sole application SPBs and their combinations with soil applied (SA) or foliar applied (FA) iron. Moreover, nutrient (N, P, K, Zn & Fe) concentrations in kernel and straw were also showed significant differences in all treatments. Findings further revealed that the combined application of SPBs + Fe-SA increased total Fe-uptake of groundnut between 24.14 to 49.75 percent while for SPBs + Fe-FA treatment this increase varied between 14.73 to 45.72 percent (over to the SPBs alone) The overall results indicated that SPBs have the potential to increase growth, yield and nutrient contents of groundnut which advocate that microbial-mediated Fe biofortification of groundnut could be a promising strategy to ameliorate Fe deficiency-induced disordering in human beings especially in developing countries.